The emotional power of capital, Cuba - Cayuela Muñoz, Ana (Revelar: Revista de Estudos da Fotografia e Imagem, 2018)
Make visible the impact that the economic political conditions have on the social behaviours of the population that live under!over them. How far can runs the inequality between humans? How do emotions are manipulated by "money"? We wanted to be honest but also ironical; using education (photography workshops) to give tools to the population with less "voice". If you can't express yourself freely or you have little internet to share or to say, so you do not count, inside of the globalized soup that our society builds. But, in case you can have a camera into your hands, you can get proofs... We documented ourselves; a tourist west woman with Cuban guys; captured or installed worlds?